EFFICACY OF DIFFERENT WEED MANAGEMENT PRACTICES ON GROWTH AND YIELD OF DIRECT WET SEEDED RICE SOWN THROUGH DRUM SEEDER - B. M. RAGHAVENDRA; R. SUSHEELA; V. PRAVEEN RAO; M. MADHAVI (The Bioscan, 2014)
An investigation was conducted to ascertain the efficacy of different weed management practices on growth and yield of direct wet seeded rice (DWSR) sown through drum seeder. Eight weed control treatments were tested in randomized block design replicated thrice. All the weed control treatments significantly reduced the population and dry weight of weeds which resulted in significantly higher growth and yield of rice over unweeded check. The weed free treatment yielded (5800 kg ha-1) significantly higher than all other treatments. Among the herbi- cides bispyribac sodium @ 25 g a.i. ha-1 at 25 DAS as PoE not only reduced population (2.89 No. m-2) and dry weight of weeds (3.43 g m-2) but also increased the grain yield (5367 kg ha-1) of rice with the concomitant increase in the yield attributes (number of panicles per meter square, panicle length and filled grains per panicle 489, 21.28 cm and 103 respectively) and which was on par with tank mixture of cyhalofop-butyl @ 100 g a.i ha-1 + Chlorimuron-ethyl + metsulfuron-methyl (@ 4 g a.i ha-1) at 15 DAS as PoE, pretilachlor + safener (0.4 kg a.i ha- 1 at 3 days after seeding) + Hand weeding at 40 DAS and two hand weeding at 20 and 40 DAS. Hence these four treatments were found to be efficient weed management practices for improving the rice grain yield by eliminat- ing early crop-weed competition in direct wet-seeded rice sown through drum seeder.